mCLCA3 does not contribute to calcium-activated chloride conductance in murine airways - Mundhenk, Lars; Johannesson, Bjarki; Anagnostopoulou, Pinelopi; Schultz, Carsten; Mall, Marcus A. (American journal of respiratory cell and molecular biology, 2012)
Ca2+-activated Cl− channels (CaCCs) contribute to airway Cl− and fluid secretion, and were implicated in the modulation of disease severity and as a therapeutic target in cystic fibrosis (CF). Previous in vitro studies suggested that members of the CLCA gene family, including the murine mCLCA3, contribute to CaCCs. However, the role of mCLCA3 in ion transport in native airway epithelia has not been studied, to the best of our knowledge. In this study, we used mCLCA3-deficient mice and determined bioelectric properties in freshly excised tracheal tissue, airway morphology, and gene expression studies, to determine the role of mCLCA3 in airway ion transport and airway structure. Bioelectric measurements did not detect any differences in basal short-circuit current, amiloride-sensitive Na+ absorption, cyclic adenosine monophosphate-dependent Cl− secretion, and activation of Ca2+-activated (uridine-5′-triphosphate-mediated) Cl− secretion in mCLCA3-deficient mice compared with wild-type mice. Moreover, no histological changes were observed in the respiratory tract or any other tissues of mCLCA3-deficient mice when compared with wild-type control mice. The intratracheal instillation of IL-13 produced an approximately 30-fold up-regulation of mCLCA3 transcripts without inducing CaCC activity in wild-type airways, and induced goblet-cell hyperplasia and mucin gene expression to similar levels in both genotypes. Further, multiple specific reverse-transcriptase quantitative PCR assays for other CaCC candidates, including mCLCA1, mCLCA2, mCLCA4, mCLCA5, mCLCA6, mCLCA7, mBEST1, mBEST2, mCLC4, mTTYH3, and mTMEM16A, failed to identify the differential expression of genes in the respiratory tract that may compensate for a lack of mCLCA3 function. Together, these findings argue against a role of mCLCA3 in CaCC-mediated Cl− secretion in murine respiratory epithelia.